The formation of grain products cluster in the Republic of Kazakhstan - Dulambaeva, R. T.; Abdulmanova, G. M. (Journal of Economic Research & Business Administration, 2015)
The problems of managing Kazakhstan’s regional development in modern economic conditions are constantly making actual the task of forming and implementing effective strategies for social and economic development of Kazakhstan’s regions. Creation of development strategies for territories based on traditional methods often do not provide for achievement of high final results and demand a new approach – formation of strategy on the basis of developing territorial clusters. Provision that is becoming a generally accepted fact is that in the conditions of globalization the internal structure is an important condition of stability and economic independence for any region, which includes the ability to adequately respond to the changes of internal and external environment of certain sectors, perform quick adaptation at the expense of innovation policy means. Competitiveness of region sis based on the efficiency of economic activity subjects working in them. For this reason cluster approach as an alternative for traditional sectorial, industrial policy represents an effective instrument for competitiveness increase of a territory.In this connection the present article unravels specific features of clusters and advantages of developing a cluster policy in Kazakhstan, and also current models of a grain products cluster which are widely used. Consideration is also given to transaction expenses of Northern Kazakhstan, model of grain products cluster and effects that are due to appear as the result of implementing cluster policy in grain sub-complex of the region.